DIASPORIC IDENTITIES AND MEDIATED EXPERIENCES IN EVERYDAY LIFE - Bailey, Olga Guedes (Passagens: Revista do Programa de Pós-Graduação em Comunicação da Universidade Federal do Ceará, 2014)
Immigration may now be considered one of the most fraught political issues in Europe. Over the past 40 years, immigration from developing countries – and now from East Europe - has changed the face of Western Europe. The periphery has moved to the centre. This move has generated western’s response towards more draconian immigration policies coupled with more nationalist discourse in the public sphere, including the media.